PERILAKU BERBAHASA AHOK: KAJIAN TINDAK TUTUR - Asmitasari Siregar, Tityn; Simpen, I Wayan; Sukartha, I Nengah (Humanis; Volume 16. No. 2. Agustus 2016, 2016)
Thesis entitled ” Perilaku Berbahasa Ahok: Kajian Tindak Tutur ” is back grounded by the using of language by Ahok which succeed stole the society interest even the experts of politic communication also involved in analyzing the using of language by Ahok especially in APBD DKI Jakarta problem. The research problems of this research are the type of speech act used by Ahok and speech act of Ahok related with surface concept. The aim of this research is to know types of speech act and surface concept used by Ahok in communication.The theories used to analyze the data are theory kinds of speech act and theory about surface concept. The research method used by the writer is descriptive qualitative method. In the collecting the data step the writer used observe method which helped by note taking technique and sorting process. The analyzing of data used descriptive method. The presentation of the result of analyzing data used formal and informal method. The speech act research of Ahok in YouTube described types of speech act used by Ahok, It is illocutionary speech act, which consist of 27 assertive speech acts, 19 directive speech acts, 6 expressive speech acts, 5 commisive speech acts, and 23 declarative speech acts. Based on the data it can be said that Ahok used assertive speech act more than commisive speech acts. The speech act of Ahok which Broke and thread the surface of speech partner, it threads positive surface of opponent speech and thread negative face of opponent speech. Based on the analyzed data, thus Ahok more often threads negative surface of speech partner.